Fractional integral operators on Herz spaces for supercritical indices - Yasuo Komori-Furuya (Journal of Function Spaces and Applications)
We consider the boundedness of fractional integral operators Iβ on Herz spaces Kqα,p(Rn), where q≥n/β. We introduce a new function space that is a variant of Lipschitz space. Our results are optimal.